Too Big? Too Small? Just Right? An Empirical Perspective on Local Firm Size Distribution and Economic Growth in U.S. Counties and High-Poverty Rural Regions. (February 2014) - Komarek, Timothy M.; Loveridge, Scott
The authors examine the relationship between the distribution of firms across size categories and economic growth, extending Loveridge and Nizalov's Michigan results to the United States. Using county-level data, including growth and control variables, the authors explore the relationship between the size distribution of firms and 12-year growth patterns for the continental United States and three multistate high-poverty regions. The results of fixed-effect feasible generalized least squares estimation show a connection between employment growth and the distribution of firms across size categories for the continental United States. The results also show a positive link between employment growth and firm size for Lineal America and the Plantation Belt, but no statistically significant relationship for the Borderlands. The results suggest that policies aimed at promoting small business, while important nationally, may differ in impacts across regions and provide an argument for region-level decision making about growth policies.